Two new species and two new records of the genus Tenuibaetis Kang & Yang, 1994 (Ephemeroptera: Baetidae) from Indian Himalaya - Kubendran, T.; Vasanth, M.; Subramanian, K. A.; Gattolliat, Jean-Luc; Selvakumar, C.; Jabeen, Fatima; Sinha, Bikramjit (Zootaxa, 2022)
As part of ongoing exploration of the mayflies of streams and rivers of Indian Himalayan regions, we describe two new species of the genus Tenuibaetis based on recently collected materials from Western Himalaya viz., Tenuibaetis himani Kubendran, Vasanth & Subramanian sp. nov. and Tenuibaetis kangi Kubendran, Vasanth & Subramanian sp. nov. Additionally, two new records from Eastern Himalaya viz., T. arduus (Kang & Yang, 1994) and T. inornatus (Kang & Yang, 1994) are presented. The biological notes of the stream/rivers are appended. A key to the known Indian species of the genus Tenuibaetis and a distribution maps are provided.